Enhancing Climate Change Adaptation & Disaster Risk Reduction in Gorakhpur - Gupta, Ankur; Gupta, Ankur; Khan, Saquib; Baghel, Gajendra Singh; Jaiswal, Manoj Kumar; Jaiswal, Vidhan (Journal of Advanced Research in Alternative Energy, Environment and Ecology; Vol 6 No 3&4 (2019): Journal of Advanced Research in Alternative Energy, Environment and Ecology, 2021)
District Gorakhpur possess severe vulnerability to earthquake and climatologically induced hazards such as drought, heat wave, cold wave, flood, hailstorm, untimely and incessant rainfall. This article gives an in-depth perspective of the need for formation of Climate Cell in Gorakhpur followed by emphasizing the ongoing and futuristic targeted approaches of District Disaster Management Authority of Gorakhpur (DDMA) for enhancing Climate Change Adaptation & Disaster Risk Reduction. Apart from the above-mentioned measures, the workshop on ‘Formation and Activation of Climate Cell in Gorakhpur’ has been discussed comprehensively in this article that led to the adoption of ‘Gorakhpur Declaration’ which is a brief outcome of the workshop. The ongoing & targeted efforts of DDMA-Gorakhpur mentioned in this article are wide expansion of green infrastructure in the district focusing on adequate plantation at adequate places; adoption of pervious pavements for urban flood mitigation; outcome of the Installation of Automatic Weather Station in SADAR sub-division of Gorakhpur; all the above mentioned activities are identified & executed by Climate Cell under the aegis of DDMA-Gorakhpur and other activity that is being done in expeditious way is formation of School Disaster Management Plan (SDMP) in Gorakhpur. In light of the vulnerability of Gorakhpur, on November 16, 2018, various stakeholders concerned with Disaster Risk Reduction (DRR) & Climate Change Adaptation (CCA) met and identified a common goal to work out for the strengthening of climate cell in Gorakhpur at the occasion of workshop. All the sessions that led to exploration of precise outcome in the workshop for enhancing the framework of CCA & DRR have been discussed in this article. How to cite this article: Gupta G, Gupta A, Khan S. Enhancing Climate Change Adaptation & Disaster Risk Reduction in Gorakhpur. J Adv Res Alt Energ Env Eco 2019; 6(3&4): 7-21. Gupta G, Gupta A, Khan S. Enhancing Climate Change Adaptation & Disaster Risk Reduction in Gorakhpur. J Adv Res Alt Energ Env Eco 2019; 6(3&4): 7-21.